PERENCANAAN RESEARCH DESIGN ARKEOLOGI BERBASIS MARKETING - Rusyanti Rusyanti (Kemendikbud, 2018)
Research planning to the realm of history and archaeology is the starting point towards the crucial impact on the work that should be done. Weaknesses in determining focus in planning, impact on the inefficiency and prolonged wastage. To overcome these problems required careful planning strategy at the initial level, i.e. by way of adapting the strategies developed in other sciences. One planning research strategy that can be use in the context of archaeology which became the idea in this article is the marketing strategy developed by Philip Kotler. The use of this frame work is to give the direction and focus of the research be more measurable, efficient, proper and exact.Keywords: Archaeology, research design, marketing